Couples coping with screening burden and diagnostic uncertainty in Li-Fraumeni syndrome: Connection versus independence. Issue 2 (4th March 2019) - Young, Jennifer L.; Pantaleao, Ashley; Zaspel, Lori; Bayer, Jessica; Peters, June A.; Khincha, Payal P.; Bremer, Renee C.; Loud, Jennifer T.; Greene, Mark H.; Achatz, Maria Isabel; Savage, Sharon A.; Werner-Lin, Allison
Abstract: Purpose: Li-Fraumeni Syndrome (LFS) is an inherited tumor predisposition syndrome with lifetime cancer risks approaching 100% and evolving risk-management strategies. This study evaluated couples' coping with LFS-related burdens. Research approach: Constructivist grounded theory and anticipatory loss frameworks guided design and analysis. Sample and methods: Twenty-six individuals enrolled in the NCI LFS Family Study completed semi-structured interviews with their partner during annual screening visits. An interdisciplinary team completed open and focused coding to identify patterns of coping and adaptation. Findings: Couples described living with ambiguous danger, a state of chronic apprehension resulting from LFS-associated uncertainties. Most couples communicated openly and alternated shouldering the burden, while others engaged in protective buffering to shield each other from distress and sustain the appearance of normalcy. Interpretation: Optimally, coping reduces shared psychosocial distress, yet some strategies may inadvertently increase disconnection. Implications: Mental health support is critical for both partners coping with LFS, together and separately.